The last romantics : [compact disc, unabridged] a novel - Conklin, Tara (Harper Audio, 2019)
In the spring of 1981, the young Skinner siblings, fierce Renee, dreamy Caroline, golden boy Joe and watchful Fiona, lose their father to a heart attack and their mother to a paralyzing depression. Caught between the predictable life they once led and an uncertain future that stretches before them, the siblings navigate the dangers and resentments to emerge fiercely loyal and deeply connected. Two decades later, the Skinners find themselves again confronted with a family crisis that tests the strength of these bonds and forces them to question the life choices they've made and what, exactly, they will do for love.